PERSPEKTIF “AL-ILM” MENURUT AL-QUR’AN DAN ULAMA SALAFI DI DALAM TATANAN PENDIDIKAN ISLAM - ummu kulsum (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
Abstract, Knowledge is the light of knowledge that is passed by reading or known as Iqra 'in the Qur'anic language, besides that many conventional scholars give meaning to the concept of "Al-Ilm". The formulation in this study a) what is the meaning of “Al-Ilm” according to the Qur'an, b) how azbabun nuzul about the verses of “Al-Ilm”, c) how the views of the salafi scholars about the concept of "Al-Ilm”, in the order of Islamic education. In that case the interpretation of maudhui is used as an implementation to interpret the concept of "Al-Ilm". The findings obtained that Al-Ilm is a way of Allah to give mandate to humans as khalifah in the world, and the knowledge given by Allah to humans needs to be sought through reading through both the qur'aniyah verses and kauniyah verses, so that the science gives benefit for humanity. Therefore, the knowledge delivered by the salafi clerics is still in the structure of Islamic education.